2006
DOI: 10.1016/j.molcel.2006.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Unliganded and Liganded Estrogen Receptors in Transcriptional Repression

Abstract: The decline in estrogen levels during menopause is associated with increased cytokine production and inflammatory diseases. Estrogens exert anti-inflammatory effects by repressing cytokine genes, such as tumor necrosis factor-alpha (TNFalpha). The mechanisms involved in transcriptional repression by estrogens are virtually unknown. Here, we used chromatin immunoprecipitation to investigate how estrogens repress the autoinduction of the TNFalpha gene. TNFalpha assembled a transcriptional activation complex at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 56 publications
3
135
2
Order By: Relevance
“…Ligand-independent functions of ERα have been described in several tissues in addition to breast cancer cells (2)(3)(4)(5). Results reported here provide a frame to understand why ERα is required to respond to aromatase inhibitors in breast cancer.…”
Section: Significancementioning
confidence: 71%
See 1 more Smart Citation
“…Ligand-independent functions of ERα have been described in several tissues in addition to breast cancer cells (2)(3)(4)(5). Results reported here provide a frame to understand why ERα is required to respond to aromatase inhibitors in breast cancer.…”
Section: Significancementioning
confidence: 71%
“…2 and references therein). Ligand-independent activity of ERα was reported by several groups on individual genes (3)(4)(5). Genomewide ERα binding in the absence of estrogen was also described in breast cancer cells acquainted with growing in hormonedepleted media (6)(7)(8) and in mouse uterus (9).…”
mentioning
confidence: 89%
“…24 A second hypothesis is that estrogen leads to the recruitment of GRIP1, which acts as a co-repressor on the TNFα promoter. 25 Alternatively, ERα has also been shown to sequester coactivators from NFκB 26 to prevent transcription of the cytokines. Other possibilities include the ability of ERα to inhibit IKK activity or degradation of IkB, thereby preventing NFκB transcriptional activation.…”
Section: The Regulation Of Osteoclastogenic Cytokines By Estrogenmentioning
confidence: 99%
“…The observation that ERa is able to bind to this region in the absence of estrogen stimulation by ChIP analysis revealed that LRP16 is a primary target of ERa. Similarly, estrogen-repressed cyclin G2, tumour necrosis factor a (TNFa) and E-cadherin genes are also ERa primary target genes (Oesterreich et al 2003, Cvoro et al 2006, Stossi et al 2006. Similar to the binding of unliganded ERa to the promoter region of LRP16 gene, the unliganded ERa can bind to the AP1/NF-kB element of TNFa promoter region and enhance its transcription; however, it will be removed from TNFa promoter region as in the case of LRP16 gene after estrogen treatment (Cvoro et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, estrogen-repressed cyclin G2, tumour necrosis factor a (TNFa) and E-cadherin genes are also ERa primary target genes (Oesterreich et al 2003, Cvoro et al 2006, Stossi et al 2006. Similar to the binding of unliganded ERa to the promoter region of LRP16 gene, the unliganded ERa can bind to the AP1/NF-kB element of TNFa promoter region and enhance its transcription; however, it will be removed from TNFa promoter region as in the case of LRP16 gene after estrogen treatment (Cvoro et al 2006). Unliganded ERa can enhance cyclin G2 transcription by binding to a 1/2 ERE/Sp1 site within its promoter, or enhance E-cadherin transcription by binding to the most proximal region of its promoter, which does not contain any classical ERE but three E-boxes.…”
Section: Discussionmentioning
confidence: 99%